Antioxidant-antidiabetic agents and human health - Oguntibeju, Oluwafemi (Rijeka, Croatia : InTech, 2014)
'The human system employs the use of endogenous enzymatic as well as non-enzymatic antioxidant defence systems against the onslaught of free radicals and oxidative stress. Enzymatic antioxidants and non-enzymatic antioxidants work synergistically with each other, using different mechanisms against different free radicals and stages of oxidative stress. Dietary and lifestyle modifications are seen as the mainstay of treatment and management of chronic diseases such as diabetes mellitus. The major aims of dietary and lifestyle changes are to reduce weight, improve glycaemic control and reduce the risk of coronary heart disease, which accounts for 70- 80% of deaths among those with diabetes. It is also important to note that medicinal plants have been used as medicines since ancient time, and continue to play significant role even in modern medicine in management and treatment of chronic diseases. Impressive numbers of modern therapeutic agents have been developed from plants. Phytochemicals have been isolated and characterised from fruits such as grapes and apples, vegetables such as broccoli and onion, spices such as turmeric, beverages such as green tea and red wine, as well as many other sources. The WHO estimates that approximately 80% of the worlds inhabitants rely on traditional medicine for their primary health care and many medicinal plants have ethno-medical claims of usefulness in the treatment of diabetes and other chronic diseases globally, and have been employed empirically in antidiabetic, antihyperlipidemic, antihypertensive, antinflammatory and antiparasitic remedies. This book examines the role of antioxidant-rich natural products in management and treatment of diabetes and other chronic diseases'--Publisher's description.
Lipid profile, antidiabetic and antioxidant activity of Acacia ataxacantha bark extract in streptozotocin-induced diabetic rats -- Oxidative stress and diabetic complications: the role of antioxidant vitamins and flavonoids -- Anti-diabetic effects of Nigerian indigenous plant foods/diets -- Some selected medicinal plants with antidiabetic potentials -- The antidiabetic activities of the aqueous leaf extract of Phyllanthus amarus in some laboratory animals -- Antidiabetic botanicals and their potential benefits in the management of diabetes mellitus -- Antioxidant-rich natural grain products and human health -- Nutritional, therapeutic, and prophylactic properties of Vigna subterranea and Moringa oleifera -- Dietary antioxidant properties of vegetable oils and nuts: the race against cardiovascular disease progression -- Plants with hypolipidaemic effects from Nigerian flora -- Garlic and its effects on health with special reference to the reproductive system -- Potentials of phytotherapeutic treatment of erectile dysfunction -- Buchu: the multi-purpose ethnomedicinally important specie and its benefits in the reproductive system -- Antioxidant-rich natural products and diabetes mellitus -- Potential role of Parkia biglobosa in the management and treatment of cardiovascular diseases.
In process PDAL
Includes bibliographical references.
Keywords: Hypoglycemic Agents -- Therapeutic use; Antioxidants -- therapeutic use; Biological Products -- therapeutic use; Antioxidants -- therapeutic use; Hypoglycemic Agents -- therapeutic use